The Implication of Pathway Turn and Task Condition on Gait Quantified Using SmartWalk: Changes With Age and Parkinson’s Disease With Relevance to Postural Strategy and Risk of Fall - Pallavi, Priya; Jariwala, Neeti; Patel, Niravkumar; Kanetkar, Manasi; Diwan, Shraddha; Lahiri, Uttama (Frontiers in Neuroscience, 2022)
One’s gait can be affected by ageing, pathway with turns, task demands, etc. causing changes in gait-related indices and knee flexion (influencing posture). Walking on pathway with turns threatens stability, affecting one’s gait-related indices and posture. Ability to overcome such deficits is compromised with age and neurological disorders, e.g., Parkinson’s Disease (PD) leading to falls. Also, task demands imposed by single and dual task (e.g., counting backwards while walking) conditions affect gait of individuals using different postural strategies varying with age and neurological disorder. Existing research has investigated either the effect of pathway with turn or task condition on one’s gait. However, none (to our knowledge) have explored the differentiated implications of pathway with turn and task condition on one’s gait-related indices and knee flexion while walking. Our study had two phases with 30 participants. Phase 1 had healthy adults (young and old) and Phase 2 had age and gender-matched healthy elderly and individuals with Parkinson’s disease who walked on pathways having turns under single and dual task conditions. We analysed gait in terms of (i)gait-related indices (Phases1 and 2) and (ii)knee flexion (Phase 2). Also, we analysed one’s counting performance during dual task. One’s gait-related indices and knee flexion were measured using portable gait quantifier. The aim was to (i)understand whether both pathway with turn and task condition are equally effective in affecting gait of (a)individuals with varying age and (b)age and gender-matched healthy older adults and individuals with Parkinson’s disease,(ii)study variations of knee joint angles while walking on pathways having turns (under different task conditions) in terms of its clinical relevance and(iii) explore the implication of pathway with turn on counting performance (with relevance to postural strategy) with varying age and PD. Results indicated that for younger group, the task condition caused statistical variations in gait-related indices. For older group, both pathway with turn and task condition had statistical implications on gait-related indices. Additionally, individuals with Parkinson’s disease demonstrated higher variation in knee flexion than their healthy counterparts. Again, pathway with varying turn elicited variations in counting performance indicating different postural strategies being employed by the three groups.